An Investigation of the Effectiveness of Government Support Structures Established to Assist SMMEs Amidst Pandemic - Lungelo Mcunu; Musawenkosi Ngibe (Contemporary Issues of Business and Management: The Proceedings of the \(10^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
This research paper investigates the effectiveness of government support structures for Small, Medium, and Micro Enterprises (SMMEs) during the COVID-19 pandemic in eThekwini Municipality, employing a positivist philosophy and a quantitative research approach. Data were collected from 201 SMME owners and managers through a structured questionnaire, analyzed using SPSS version 28.0, reveals significant challenges faced by SMMEs, including supply chain disruptions, inventory shortages, cash flow issues, reduced income, difficulties accessing government support, exclusion of informal traders, insufficient innovative training, inadequate economic policies, and limited awareness of government initiatives. Despite these challenges, positive results from government support structures included financial relief programs, training and advisory services, and platforms promoting SMMEs, though their effectiveness was constrained by communication and implementation gaps. To address these issues, it is recommended that government support structures expand funding accessibility, develop tailored training programs, provide clear feedback on funding applications, and enhance the visibility of initiatives while encouraging SMMEs to proactively seek funding opportunities. These measures would help identify gaps, provide targeted support, and better inform SMMEs, mitigating challenges and fostering growth. The study concludes that inadequate communication and understanding of government initiatives hindered many SMMEs from accessing available resources, highlighting the need for improved outreach and support mechanisms.